PENGARUH DISIPLIN KERJA DAN KUALITAS PELAYANAN TERHADAP KINERJA KARYAWAN DIVISI CLEANING SERVICE PADA PT. BINAR EMBUN SERVIS KABUPATEN TANGERANG - Mohamad Hadi Santoso; Hamdi Supriadi (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the effect of work discipline on employee performance at PT. Binar Dew Services, Service quality on employee performance at PT. Binar Dew Services and the Influence of Work Discipline and Service Quality on employee performance at PT. Binar Dew Services. This research uses quantitative methods by distributing questionnaires to some PT employees. Binar Dew Services Tangerang Regency, totaling 98 respondents, used a slovin sampling technique with a precision of 5%. The data obtained was then processed using SPSS statistical software version 20. This analysis technique includes validity tests, reliability tests, classical assumption tests, multiple linear regression analysis test, correlation coefficient tests, coefficient of determination tests, and statistical tests via the t test. , and F test. The results of the t test show that Work Discipline and Service Quality partially have a positive and significant effect on employee performance. Meanwhile, the F test shows that work discipline and service quality simultaneously have a positive and significant effect on employee performance. The correlation coefficient is 0.637, meaning that the three variables have a strong level of relationship. The R Square coefficient of determination value was found to be 0.406, meaning that the influence of the Work Discipline and Service Quality variables on employee performance is 40.6%, while the remaining 59.4% is explained by other variables. which is not discussed in this research. The research results show that: 1) Work Discipline partially has a positive and significant effect on employee performance at PT. Binar Dew Services Tangerang Regency. 2) Service Quality partially has a positive and significant effect on employee performance at PT. Binar Dew Services Tangerang Regency. 3) Work Discipline and Service Quality simultaneously have a significant effect on employee performance at PT. Binar Dew Services Tangerang Regency.